Computational methods and clinical applications in musculoskeletal imaging : 6th International Workshop, MSKI 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16, 2018, Revised selected papers /: 6th International Workshop, MSKI 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16, 2018, Revised selected papers. (2019) - Unknown
No abstract available